1992
DOI: 10.1093/intimm/4.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of Th2 cells in murine Peyer's patches by oral immunization

Abstract: We have used three different methods to determine the T helper (Th) cell response, including Th1 and Th2 types, in murine Peyer's patches (PP) following oral immunization with sheep red blood cells (SRBC). These include: (i) use of cytokine-specific (IFN-gamma and IL-5), single cell assays to estimate the frequencies of Th1 and Th2 cells respectively, (ii) cytokine-specific mRNA--cDNA dot blot and Northern gel hybridizations to detect levels of specific mRNA, and (iii) T cell cloning techniques to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 0 publications
5
46
1
1
Order By: Relevance
“…In addition, the prolonged IgA responses resembled the observed time course described for oral immunization with microencapsulated DNA (18,33,34). As formulated, the mucosal delivery of the protein 1-PL-DNA favored Th2-type cytokine responses consistent with previous reports that vaccination of mucosal surfaces favors Th2-type development (12,35,36). The reason for this preferential Th2-type bias is unclear, because a recent report showed that i.n.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the prolonged IgA responses resembled the observed time course described for oral immunization with microencapsulated DNA (18,33,34). As formulated, the mucosal delivery of the protein 1-PL-DNA favored Th2-type cytokine responses consistent with previous reports that vaccination of mucosal surfaces favors Th2-type development (12,35,36). The reason for this preferential Th2-type bias is unclear, because a recent report showed that i.n.…”
Section: Discussionsupporting
confidence: 88%
“…PP is an intestinal lymphoid organ and is characterized as an inductive site of mucosal-type immune responses such as Th2 cytokines and transforming growth factor (TGF-b) secretion. 14,15) It has been reported that DC in PP preferentially induced Th2 cytokines, while SPL DC induced Th1 cytokines. 9,10) Our present study shows that antigen presentation by whole PP cells could induce both Th1-and Th2-type cytokine patterns.…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 is often considered a Th2-type cytokine (48,49). However, its exact regulation in relation to IL-4 production in the intestine is not clearly understood, and to this point it has not been studied in intestinal GVHR.…”
Section: Il-4 and Il-5 Production From Cells In Systemic Intestinalmentioning
confidence: 99%